Flammability of Polyester and Epoxy Resins by Using Some of a New Organic Compounds - Farhan Jawad, Sabrean; Adnan, Shaimaa; N. Al-baiati, Mohammad (International Journal of Psychosocial Rehabilitation, 2020)
In this work, seven additives were used, namely: (5-(6-bromobenzothiazol-2-yl)diazenyl)-2-hydroxybenzaldehyde) (Additive I), (5-6-bromobenzothiazol-2-yl)diazenyl)-2-hydroxyphenyl) -1-(4-hydroxy-3-methoxyphenyl)prop-2-en-1-one) (Additive ), 5,6-(bromobenzothiazol-2-yl)diazenyl)-2-hydroxyphenyl) -1-(4-prop-2-en-1-one (Additive III), 5-6-bromobenzothiazol-2-yl)diazenyl)-2-hydroxyphenyl) -1-(4-methoxyphenyl)prop-2-en-1-one (Additive IV), 4-6-bromobenzothiazol-2-yl)diazenyl)-2-2-hydroxy-5-methylphenyl)imino)methyl)phenol (Additive V).4-6-bromobenzothiazol-2-yl)diazenyl)-2-2-hydroxy-5-methylphenyl)imino)methyl)phenol (Additive VI) and (1E)-N-(5-((6-bromobenzo[d]thiazol-2-yl)diazenyl)-2-hydroxybenzylidene)-N'-(4-chlorophenyl)formimidamide (Additive VII). The effects of these additives on the flammability of some of the thermosetting polymers (unsaturated polyester and epoxy resins) have been studied. Sheets of the specimens (resins with different weight percentages of additives), in dimensions (150X150X3) mm, were prepared. Two standard test methods are used to measure flame retardation, which are ASTM D-2863 and ASTM D-635. Results are obtained from these tests indicating that additive 6A has high efficiency as a flame retardant, self-extinguishing (S.E.) at the percentage (0.1 %) for unsaturated polyester and the epoxy resins. Also self-extinguishing (S.E.) at the percentage (0.1%) for additives 1A, 4A, and 5A in unsaturated polyester resin, and nonburning occurs in 0.15% with additives 6A and 5A in unsaturated polyester resin, but it occurs in 0.2% with additives 6A and 5A in epoxy resin. Additive A shows a low effect on flammability in both resins.